Development and evaluation of a health literacy training program for allied health professionals: A pre‐post study assessing impact and implementation outcomes. (26th May 2020) - Muscat, Danielle M.; Ceprnja, Dragana; Hobbs, Kim; Gibson, Jodi‐Anne; Blumenthal, Caron; Milad, Rula; Burns, Chris; Lau, Timothea; Flood, Victoria
Abstract: Issue addressed: We developed and evaluated a health literacy training program for allied health professionals, and explored the feasibility of a train‐the‐trainer model to support dissemination. Methods: The program combined didactic and experiential teaching methods and behaviour change techniques, with a focus on teach‐back and developing easy‐to‐understand written materials. Outcomes included participant reactions, confidence (range: 6‐30), behavioural intentions (range: 6‐42), and dissemination of training content. Implementation outcomes were evaluated using the Normalization MeAsure Development (NoMAD) tool, assessing the constructs of coherence (range: 4‐20), cognitive participation (range: 4‐20), collective action (range: 7‐35) and reflexive monitoring (range: 5‐25). Results: Of the 29 allied health professionals who participated, 90% rated the program as 'excellent'/'very good', and 97% said the information was 'extremely'/'very' helpful for their everyday practice. We observed increases in confidence (mean difference [MD] = 6.3, standard deviation [SD] = 2.7, t25  = 11.87, P  < .001) and intentions (MD = 3.6, SD = 8.1, t23  = 2.2, P  = .04) related to health literacy practices after 6 weeks. Improved confidence was retained over 6 months (MD = 7.1, SD = 5.2, t18  = 5.96, P  < .001). After 6 months, 95% of participants (n = 19) reported using teach‐back and 50% (n = 10) reported having used a readability formula. Eight‐five per cent of participants (17/20) had trained others in health literacy, reaching n = 201 allied health professionals and students. NoMAD scores were highest in relation to cognitive participation (/20) (M = 18.2, SD = 2.1) and lowest in relation to collective action (/35) (M = 25.4, SD = 3.0). Conclusions: A train‐the‐trainer model appears to be a feasible method to disseminate health literacy training, but additional work may be needed to improve the collective work done to enable health literacy practices in real‐world clinical contexts. So what: Staff training is particularly important in highly diverse areas where patients are disproportionately affected by low health literacy.